2018
DOI: 10.1097/01.aoa.0000542311.02864.ad
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intrathecal Bupivacaine Dose on the Success of External Cephalic Version for Breech Presentation: A Prospective, Randomized, Blinded Clinical Trial

Abstract: (Anesthesiology 2017;127:625–632) Increased rate of cesarean delivery without measurable improvements in maternal or neonatal outcomes is a major public health problem. Breech presentation is a major contributor to the incidence of cesarean delivery and can be prevented by external cephalic version (ECV). Neuraxial blockade for ECV improves maternal satisfaction and procedural success and decreases maternal pain. Meta-analysis of randomized controlled trials suggests that administering higher doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Regarding the effective dose, a recent RCT compared four doses of spinal bupivacaine (10, 7.5, 5 and 2.5 mg þ fentanyl 15 mg) and concluded that doses above 2.5 mg offered no additional benefit for ECV success rate or prevention of Caesarean deliveries. 4 This study reported a mean sensory level of T6 and adequate abdominal wall relaxation in all groups. While lower doses of spinal anaesthesia may suffice for ECV and facilitate an earlier discharge, a larger dose of spinal bupivacaine would facilitate an emergency Caesarean delivery if needed.…”
Section: Neuraxial Blockmentioning
confidence: 50%
“…Regarding the effective dose, a recent RCT compared four doses of spinal bupivacaine (10, 7.5, 5 and 2.5 mg þ fentanyl 15 mg) and concluded that doses above 2.5 mg offered no additional benefit for ECV success rate or prevention of Caesarean deliveries. 4 This study reported a mean sensory level of T6 and adequate abdominal wall relaxation in all groups. While lower doses of spinal anaesthesia may suffice for ECV and facilitate an earlier discharge, a larger dose of spinal bupivacaine would facilitate an emergency Caesarean delivery if needed.…”
Section: Neuraxial Blockmentioning
confidence: 50%
“…Several studies have used analgesia 8, [12][13][14]16,20,23 and tocolysis 8,11 to improve the ECV success rate. The present study had remarkable procedure characteristics such us, as far as we are concerned, it is the first study in which propofol is used for ECV and what tocolysis concerned, ritodrine is administered for 30 minutes just before the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…About analgesia in ECV, some interventions have been analyzed such as systemic opioids or spinal anesthesia. Spinal anesthesia techniques improve the ECV success rate and pain after procedure [13][14][15][16] . No differences are reported in Ethe CV success rate when systemic opioids or spinal anesthesia are compared 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies proved that analgesia [8,[12][13][14][15][16]20] and tocolysis [8,11] improve the ECV success rate. The present study had remarkable procedure characteristics such us, as far as we are concerned, it is the first group in which propofol is used for deep sedation in ECV, and what tocolysis concerned, ritodrine is administered for half-hour just before the procedure [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Other analgesic agents have been analyzed such as systemic opioids or spinal anesthesia. Spinal anesthesia techniques improve the ECV success rate and pain after the procedure [13][14][15][16]. No differences are reported in the ECV success rate when systemic opioids or spinal anesthesia are compared [13].…”
Section: Certain Interventions Facilitate Ecvmentioning
confidence: 99%